Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's solve the problem step-by-step.
We are given the equation:
[tex]\[ 2a - b + c = 0 \][/tex]
We need to demonstrate that:
[tex]\[ 4a^2 - b^2 + c^2 + 4ac = 0 \][/tex]
First, let's express [tex]\(b\)[/tex] in terms of [tex]\(a\)[/tex] and [tex]\(c\)[/tex] from the given equation [tex]\(2a - b + c = 0\)[/tex]:
[tex]\[ 2a + c = b \][/tex]
Now, we substitute [tex]\(b = 2a + c\)[/tex] into the expression we need to prove:
Consider the expression [tex]\(4a^2 - b^2 + c^2 + 4ac\)[/tex]:
By substituting [tex]\(b = 2a + c\)[/tex], the expression becomes:
[tex]\[ 4a^2 - (2a + c)^2 + c^2 + 4ac \][/tex]
Next, let's expand [tex]\((2a + c)^2\)[/tex]:
[tex]\[ (2a + c)^2 = 4a^2 + 4ac + c^2 \][/tex]
Now, substitute this expansion back into our expression:
[tex]\[ 4a^2 - (4a^2 + 4ac + c^2) + c^2 + 4ac \][/tex]
Simplify this step-by-step:
[tex]\[ = 4a^2 - 4a^2 - 4ac - c^2 + c^2 + 4ac \][/tex]
Combine like terms:
[tex]\[ = 4a^2 - 4a^2 - 4ac - c^2 + c^2 + 4ac \][/tex]
Notice that everything cancels out:
[tex]\[ = 0 \][/tex]
Thus, we have shown that:
[tex]\[ 4a^2 - b^2 + c^2 + 4ac = 0 \][/tex]
Therefore, given [tex]\(2a - b + c = 0\)[/tex], we've proven that [tex]\(4a^2 - b^2 + c^2 + 4ac = 0\)[/tex].
We are given the equation:
[tex]\[ 2a - b + c = 0 \][/tex]
We need to demonstrate that:
[tex]\[ 4a^2 - b^2 + c^2 + 4ac = 0 \][/tex]
First, let's express [tex]\(b\)[/tex] in terms of [tex]\(a\)[/tex] and [tex]\(c\)[/tex] from the given equation [tex]\(2a - b + c = 0\)[/tex]:
[tex]\[ 2a + c = b \][/tex]
Now, we substitute [tex]\(b = 2a + c\)[/tex] into the expression we need to prove:
Consider the expression [tex]\(4a^2 - b^2 + c^2 + 4ac\)[/tex]:
By substituting [tex]\(b = 2a + c\)[/tex], the expression becomes:
[tex]\[ 4a^2 - (2a + c)^2 + c^2 + 4ac \][/tex]
Next, let's expand [tex]\((2a + c)^2\)[/tex]:
[tex]\[ (2a + c)^2 = 4a^2 + 4ac + c^2 \][/tex]
Now, substitute this expansion back into our expression:
[tex]\[ 4a^2 - (4a^2 + 4ac + c^2) + c^2 + 4ac \][/tex]
Simplify this step-by-step:
[tex]\[ = 4a^2 - 4a^2 - 4ac - c^2 + c^2 + 4ac \][/tex]
Combine like terms:
[tex]\[ = 4a^2 - 4a^2 - 4ac - c^2 + c^2 + 4ac \][/tex]
Notice that everything cancels out:
[tex]\[ = 0 \][/tex]
Thus, we have shown that:
[tex]\[ 4a^2 - b^2 + c^2 + 4ac = 0 \][/tex]
Therefore, given [tex]\(2a - b + c = 0\)[/tex], we've proven that [tex]\(4a^2 - b^2 + c^2 + 4ac = 0\)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.